Acceptance of Recommendations by Inpatient Pharmacy Case Managers: Unintended Consequences of Hospitalist and Specialist Care. Issue 1 (10th January 2013) - Anderegg, Sammuel V.; DeMik, David E.; Carter, Barry L.; Dawson, Jeffrey D.; Farris, Karen; Shelsky, Constance; Kaboli, Peter
<x xml:space="preserve">Abstract</x> Study Objective To determine whether recommendations made by pharmacists and accepted by hospital physicians resulted in fewer postdischarge readmissions and urgent care visits compared with recommendations that were not implemented. Design Prospective substudy of pharmacist recommendations. Setting Tertiary care academic medical center and private community‐based physician practices and community pharmacies. Patients A total of 192 patients aged 18 years or older who were a subsample of a randomized, prospective study, who were admitted with a previous diagnosis of one of nine cardiovascular or pulmonary diseases or diabetes mellitus or had received oral anticoagulation therapy and who were discharged to community‐based care provided by private physicians and community pharmacists. Measurements and Main Results Pharmacy case managers performed evaluations for patients and made recommendations to inpatient physicians. Patients received drug therapy counseling, a drug therapy list, and a wallet card at discharge. Data were collected from patients and private physicians for 90 days after discharge. Pharmacy case managers made 546 recommendations to inpatient physicians for 187 patients (97%). Overall, 260 (48%) of the 546 recommendations were accepted. The acceptance rate was lower for patients who had an urgent care visit compared with the other patients (33.6% vs 52.2%, p=0.033). High acceptance rates were noted for updating the record after medication reconciliation (36 patients [78%]) and when there was an actual allergy (2 [100%] of 2 patients) or medication error (2 [100%] of 2 patients). Physicians were less likely to accept recommendations related to drug indications (p<0.001), drug efficacy (p=0.041), and therapeutic drug and disease state monitoring (p=0.011). Recommendations made for patients with a relatively greater number of drugs were also less likely to be accepted (p=0.003). Conclusion Recommendations to reconcile medications or address actual drug allergies or medication errors were frequently accepted. However, only 48% of all recommendations were accepted by inpatient physicians, and there was no impact on health care use 90 days after discharge. This study suggests that recommendations by pharmacy case managers were underused, and the low acceptance rate may have reduced the potential to avoid readmissions.